Enhanced perfume surface delivery to interfaces using surfactant surface multilayer structures - Brabury, R; Penfold, J; Thomas, R; Tucker, I; Petkov, J; Jones, C (Elsevier, 2015)
Enhanced surface delivery and retention of perfumes at interfaces are the keys to their more effective and efficient deployment in a wide range of home and personal care related formulations. It has been previously demonstrated that the addition of multivalent counterions, notably Ca2+, induces multilayer adsorption at the air–water interface for the anionic surfactant, sodium dodecyl-6-benzenesulfonate, LAS-6. Neutron reflectivity, NR, measurements are reported here which demonstrate that such surfactant surface multilayer structures are a potentially promising vehicle for enhanced delivery of perfumes to interfaces. The data show that the incorporation of the model perfumes, phenylethanol, PE, and linalool, LL, into the surface multilayer structure formed by LAS-6/Ca2+ results in the surface structures being retained up to relatively high perfume mole fractions. Furthermore the amount of perfume at the surface is enhanced by at least an order of magnitude, compared to that co-adsorbed with a surfactant monolayer.